Heuristics and general principles of learning. - Mazur, James E (Behavioural Processes, 2005)
This research on decision-making heuristics is similar to research on animal learning in at least two ways. First, optimality modeling has not proven to be very useful for either research area. Second, both of these research areas seek to find general principles (or heuristics) that are applicable to different species in different settings. However, the basic principles of classical and operant conditioning seem to be more uniform across species and situations, whereas decision-making heuristics can vary for different species and different situations, even for tasks with very similar characteristics.
0 citations (Crossref) [2023-10-31] Place: Netherlands Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Algorithms; *Decision Making; *Learning; *Models; Psychological; Animalia; Animals; Decision-making; Heuristics; Humans; Optimality modeling; behavioral research; conditioned reflex; conference paper; decision making; dept.psy; heuristics; human; instrumental conditioning; learning; mental task; nonhuman